PERUBAHAN OPINI AUDIT DAN LABA TAKTERDUGA TERHADAP WAKTU PENYAMPAIAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN BASIC INDUSTRY & CHEMICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014) - Kurniawati Kurniawati (Jurnal Akuntansi Bisnis, 2017)
The aims of this research are to investigate the influence of audit opinion changes and unexpected earnings to the submission of financial statements (measured by Financial Reporting Lead Time - FRLT). Audit opinion changes is seen if opinion be better over the next year (improvement in audit opinion) and if opinion be worse over the next year (deterioration in audit opinion). The sample used in this research were company listed at Indonesia Stock Exchange that included in basic industry & chemicals 2012-2014. Samples are collected by purposive sampling and resulted in 42 firms as the final sample. The statistic method used was multiplied analysis linear regression, with hypotheses testing of statistic t tests.The results of this research showed that the audit opinion changes (both improvement and deterioration in audit opinion) has a significant influence to the financial reporting lead time , while unexpected earnings and financial leverage has no significant influence to the financial reporting lead time.Keywords: Audit opinion changes, unexpected earnings, leverage, improvement in audit opinion, deterioration in audit opinion, financial reporting lead time